Evidence for Nonlinear Asymmetric Causality in US Inflation, Metal, and Stock Returns - D. Hristu-Varsakelis; C. Kyrtsou (Discrete Dynamics in Nature and Society)
The purpose of this paper is to propose a version of causality testing that focuses on how the sign of the returns affects the causality results. We replace the traditional VAR specification used in the Granger causality test by a discrete-time bivariate noisy Mackey glass model. Our test reveals interesting and previously unexplored relationships in US economic series, including inflation, metal, and stock returns.